Methods of Art Therapy in Extracurricular Activities for Children with ASD as an Instruments of Forming of the Empathy to Peers - E.E. Artemova; M.A. Ryazhenova (Moscow State University of Psychology and Education, 2020)
The article considers the problem of lack of empathy and responsiveness to peers in children with autism spectrum disorders. The difficulties in the formation of social interaction in primary school children with autism spectrum disorders are the subject of discussion of special pedagogics and psychology. The article describes the experience of using art therapy methods in order to form a sense of responsiveness to peers in junior students with autism spectrum disorders. The authors give recommendations on the application of picture therapy, music therapy, play therapy and fairy tale therapy in extracurricular activities. Comparative results of the primary and repeated diagnostics of the formation of interaction skills of primary schoolchildren with ASD allow us to speak about the effectiveness of the described methods of psycho-correctional work.